How Do Mandarin Chinese Children Build Bridges? A Syntax-Discourse Processing Model of Referential Dependencies and its Application - Xie, Yuan (LOT, 2021)
In this dissertation, I explored how Mandarin Chinese children from 3 to 6 years old acquire knowledge of referential dependencies at the syntax-discourse interface. Such dependencies require a form of bridge building between the element ziji (self-) and an antecedent like Zhangsan, or between a definite noun phrase like zuozhe (the author) and an earlier mentioned noun phrase like (yi)-ben shu (a book). In order to achieve this goal, I first built a Syntax-Discourse-Processing model to describe the mechanisms of referential dependencies in Mandarin Chinese. This model is needed because purely syntactic theories and purely discourse theories are both insufficient to explain various referential dependencies. The model proposed takes both the morphosyntactic features and discourse factors into consideration, with a processing and computational flavor, providing new insights into existing syntactic and discourse theories on referential dependencies. With this model, I then conducted two language comprehension experiments to test Mandarin Chinese children’s knowledge of referential dependencies. The findings show that Mandarin children begin to demonstrate syntax-discourse interface knowledge at a very early age. Specifically, they know how to build a bridge between ziji and its antecedent, as well as a bridge between a definite noun phrase and its antecedent, at around 3 to 4 years old, and after the age of 4 they show fully adult-like behavior. These acquisition profiles of Mandarin Chinese children can also provide data for a general comparison with their Dutch counterparts in previous studies and offer support for the newly proposed model.
Keywords: child language acquisition; syntax-discourse interface; Mandarin Chinese; reflexives; bridging; processing model